THE EFFECT OF TAX PLANNING, FIRM SIZE, AND CAPITAL STRUCTURE ON FIRM VALUE (STUDY ON MANUFACTURING COMPANIES IN THE FOOD AND BEVERAGE SUB-SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2019–2024) - Rini Dyah Puspo Sari; Maya Safira Dewi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of tax planning, firm size, and capital structure on firm value in food and beverage manufacturing companies listed on the Indonesia Stock Exchange during the 2019–2024 period. This research uses a quantitative method with descriptive and verificative approaches. The data used are secondary data obtained from company financial statements and analyzed using panel data regression with the assistance of EViews 13 software. The results show that tax planning, firm size, and capital structure affect firm value. This indicates that tax management, company assets, and funding policies are factors considered by investors in assessing a company. In addition, these three variables simultaneously influence firm value. This study is expected to serve as a consideration for companies in determining appropriate financial policies to increase firm value. Furthermore, this research is also expected to become a reference for investors.